MULTI-CHOICE STOCHASTIC TRANSPORTATION PROBLEM INVOLVING LOGISTIC DISTRIBUTION - Agrawal, Prachi; Ganesh, Talari (Advances and applications in mathematical sciences, 2018)
In Mathematical Programming, the decision makers have freedom to choose best choices to optimize each objective. This paper aims to describe the multi-choice stochastic transportation problem (MCSTP) and its solution procedure. By considering the supply and demand as parameters and treated as independent random variables which follow Logistic distribution. The cost coefficients of the objective function are in multi-choice type. The stochastic transportation problem (STP) converted to a deterministic problem and multi-objective function have converted into a single objective using binary variables. With the help of a numerical example, explained the methodology and technique for converting the multi-objective to a single objective. The main motive is to minimize the transportation cost which satisfies the requirements according to availability of the product.